Rethinking the Keynesian revolution : Keynes, Hayek, and the Wicksell connection - Goodspeed, Tyler Beck. (New York ; Oxford : Oxford University Press, 2012)
While standard accounts of the 1930s debates surrounding economic thought pit John Maynard Keynes against Friedrich von Hayek in a clash of ideology, this dichotomy is in many respects superficial. This book argues that both Keynes and Hayek developed their theories of the business cycle within the tradition of Knut Wicksell.
Includes bibliographical references and index.
Description based on online resource; title from PDF title page (viewed on July 9, 2012).
Keywords: Keynes, John Maynard, -- 1883-1946.; Hayek, Friedrich A. von -- 1899-1992.; Wicksell, Knut, -- 1851-1926.; Keynesian economics